Implementing Differentiated Learning in Inclusive Schools: Challenges and Teacher Practices in Accommodating the Needs of Students with Special Needs - Sitihardiyanti Yusuf; Suparno Suparno; Atien Nur Chamidah; Nur Azizah; Achmad Salido (JENIUS (Journal of Education Policy and Elementary Education Issues), 2025)
Inclusive education provides opportunities for students with special needs and regular students to learn together in one educational environment. In this context, differentiated learning becomes a strategy that allows teachers to design instruction according to the needs, learning styles, and readiness of both regular and special-needs students. This study aims to identify and gather information on the implementation of differentiated learning in inclusive schools, with an emphasis on teachers' roles in accommodating the needs of students with special needs. The research method used was descriptive qualitative through interviews with inclusive schools in Gorontalo City. The results show that teachers face challenges in differentiating content, processes, and learning products, especially for students with special needs. However, teachers continue to strive to implement various adaptation practices, such as utilizing supporting learning methods and media. This study emphasizes the importance of teachers' roles in implementing differentiated learning to accommodate student diversity in the context of inclusive education.